THE DEVELOPMENT OF CANVA TO ENHANCE LEARNING OUTCOMES AND CHARACTER OF GRADE 1 IN ACCORDANCE WITH THE NATURE OF THE TIME - Hariratul Mahya, Berlian; Ngabiyanto; Sholeh, Muh; Kurniawan, Edi; Eko Armaidi, Indriana; Joko Raharjo, Tri; Yusuf, Amin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Observations carried out in Class 1 at Bakalrejo 2 State Primary School indicate that the teaching methods employed still tend to lack variety. The existing teaching is limited to the use of learning media, which has an impact on the low learning outcomes and character development of students. One solution to overcome this is to utilise Canva learning media. The aim of this study is to develop, test the feasibility of, and assess the effectiveness of Canva learning media on the learning outcomes and character of students in Class 1 of Bakalrejo 2 State Primary School, in line with the demands of the times. This study employed a research and development (R&D) methodology using the Borg and Gall model. Based on the research findings, the implementation of Canva media achieved a feasibility percentage of 95% and 90% following evaluation by subject matter and media experts. According to the effectiveness test using the t-test, significant values of 0.001 and 0.000 were obtained on the small and large scales, respectively. Meanwhile, the N-Gain calculation yielded a figure of 0.7737 in the small-scale trial and 0.7683 in the large-scale trial, both falling into the ‘high’ category. Based on these findings, it can be concluded that the use of Canva is effective in enhancing both academic achievement and moral character among students in the subject of Pancasila Education, particularly regarding the topic of rules within the home.